Geographical routing and participant collaboration model based communication mechanism of WSAN - Haijun ZHAO; Chunlin HE; Bin PU; Mengtian CUI (Tongxin xuebao)
The communication mechanism of wireless sensor and actor network (WSAN) was studied.Firstly,a proactive location management mechanism based on the update messages sent by mobile actors to sensors and the actors’ scope limited by Voronoi diagram was proposed.Thus,sensors predicted the movement of actors using Kalman filtering of the previously received updates.Then,an optimal energy-aware forwarding rule based on geographical routing was presented for sensor-actor communication,and the delay of the data delivery process was controlled using the power control and the network congestion was dealed with by forcing multiple actors to share the traffic generated in the event area.Finally,based on the characteristics of multiple concurrent events,a model for actor-actor coordination was proposed to coordinate their movements in order to optimally accomplish the tasks.Performance simulation results show that the proposed cooperative communication mechanism for WSAN can effectively reduce end-to-end delays,energy consumption and percentage of packet drops.